2023
DOI: 10.1038/s41467-023-43568-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell epigenomics and spatiotemporal transcriptomics reveal human cerebellar development

Suijuan Zhong,
Mengdi Wang,
Luwei Huang
et al.

Abstract: Human cerebellar development is orchestrated by molecular regulatory networks to achieve cytoarchitecture and coordinate motor and cognitive functions. Here, we combined single-cell transcriptomics, spatial transcriptomics and single cell chromatin accessibility states to systematically depict an integrative spatiotemporal landscape of human fetal cerebellar development. We revealed that combinations of transcription factors and cis-regulatory elements (CREs) play roles in governing progenitor differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Such cross-species differences are unlikely to be attributed to the data quality, given that the extremely high expression levels of MGP and NPY were detected in human. Furthermore, though HEY1 was suggested as a critical regulator of GC lineage development 27 , different expression patterns of HEY1 could be observed between human and mouse. Hey1 was almost co-expressed with Atoh1 in mouse, while it was confined in a small fraction of human ATOH1 + GC progenitors (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Such cross-species differences are unlikely to be attributed to the data quality, given that the extremely high expression levels of MGP and NPY were detected in human. Furthermore, though HEY1 was suggested as a critical regulator of GC lineage development 27 , different expression patterns of HEY1 could be observed between human and mouse. Hey1 was almost co-expressed with Atoh1 in mouse, while it was confined in a small fraction of human ATOH1 + GC progenitors (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have applied single cell technologies to investigate the details of mouse cerebellar development from embryonic to postnatal stages 15 24 . However, our understanding of human cerebellar development is relatively limited 25 27 . Here, we adopted single-cell multi-omics approaches, including single-cell RNA sequencing (scRNA-seq), single-cell sequencing assay for transposase-accessible chromatin (scATAC-seq) and spatial transcriptomics, to delineate the developmental landscape of human cerebellum at high spatial-temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies that have identified new subpopulations and transcriptional heterogeneity in what were previously thought to be homogeneous compartments by ST techniques, including the discovery of LeprþCxcl12-enriched reticulocytes as a major source of pro-hematopoietic factors, and there have also been studies that have clarified the molecular characterization and localization of bone marrow-resident cell types(Al-Sabah et al 2019 ). In addition, differentiation and development in the heart, brain, endocrine, and other tissues are continuing to deepen with ST technologies (Fan et al 2023 ; Luo et al 2021 ; Mantri et al 2021 ; Matsumoto and Yamamoto 2024 ; Zhong et al 2023 ), improving our knowledge of human development and related diseases. In conclusion, ST is a valuable tool for the study of stem cell biology and can provide important insights into the molecular mechanisms of stem cell development and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that there is a growing interest in this field worldwide, with the United States being the leading country with the most publications and China being one of the most active major players, but collaboration and communication among countries and institutions needs to be strengthened. The cutting-edge directions and hotspots in this field are tissue recognition, cancer, heterogeneity, immunotherapy, differentiation, and artificial intelligence model (Covert et al 2023 ; Li et al 2022a , 2022b ; Liu et al 2023 ; Williams et al 2022 ; Zhong et al 2023 ). Updates in ST technology have provided higher precision and accuracy for tissue recognition, allowing a more comprehensive study of tissues at the molecular level.…”
Section: Discussionmentioning
confidence: 99%